2023
DOI: 10.3390/ijms241612699
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier Breakdown in Neuroinflammation: Current In Vitro Models

Sarah Brandl,
Markus Reindl

Abstract: The blood–brain barrier, which is formed by tightly interconnected microvascular endothelial cells, separates the brain from the peripheral circulation. Together with other central nervous system-resident cell types, including pericytes and astrocytes, the blood–brain barrier forms the neurovascular unit. Upon neuroinflammation, this barrier becomes leaky, allowing molecules and cells to enter the brain and to potentially harm the tissue of the central nervous system. Despite the significance of animal models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 326 publications
(418 reference statements)
0
1
0
Order By: Relevance
“…The brain cells receive copper from the BBB and through the BCB, with choroid plexus cells playing a key role in regulating copper entry into the CSF and endothelial cells of intraparenchymal capillaries regulating copper entry into the brain parenchyma [ 27 ]. In recent years, the neurovascular unit (NVU) has been introduced in the literature as a collective term including all cell types participating in the integrity of the BBB: brain microvascular endothelial cells (BMECs), pericytes, astrocytes, neurons, microglia, and oligodendrocytes [ 28 ]. The highest rate of copper ions’ transport into the brain parenchyma, compared to the CSF, clearly indicates that the BBB is the principal site through which copper enters the CNS [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The brain cells receive copper from the BBB and through the BCB, with choroid plexus cells playing a key role in regulating copper entry into the CSF and endothelial cells of intraparenchymal capillaries regulating copper entry into the brain parenchyma [ 27 ]. In recent years, the neurovascular unit (NVU) has been introduced in the literature as a collective term including all cell types participating in the integrity of the BBB: brain microvascular endothelial cells (BMECs), pericytes, astrocytes, neurons, microglia, and oligodendrocytes [ 28 ]. The highest rate of copper ions’ transport into the brain parenchyma, compared to the CSF, clearly indicates that the BBB is the principal site through which copper enters the CNS [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The blood-brain barrier (BBB) is essential for maintaining the brain's microenvironment. Recent studies have revealed that presenilin is involved in BBB integrity through interactions with a reduced barrier function, reduced drug efflux pump activity, and dimin-ished glucose metabolism [47,48] Dysfunction of the BBB can lead to increased neuroinflammation and infiltration of peripheral immune cells, exacerbating AD pathology [49].…”
Section: Presenilin and Synaptic Dysfunction And Neuronal Lossmentioning
confidence: 99%
“…Research has also shown that aging, cerebrovascular accident (CVA), carcinogenetic neoplasms, infections, injuries, ischemic events, neuroinflammation, neurodegenerative diseases (i.e., AD), and hydrocephalus may compromise these protective barrier structures, permeability, and functionality and potentially increase the BBB's permeability [93][94][95].…”
Section: Challenges Of Delivering Prime Editors To the Brainmentioning
confidence: 99%
“…Research has also shown that aging, cerebrovascular accident (CVA), carcinogenetic neoplasms, infections, injuries, ischemic events, neuroinflammation, neurodegenerative diseases (i.e., AD), and hydrocephalus may compromise these protective barrier structures, permeability, and functionality and potentially increase the BBB’s permeability [ 93 , 94 , 95 ]. Moreover, in vitro studies on SARS-COVID-19 SARS-CoV-2 pathogens have indicated that the pathogens’ S1 and S2 spike proteins trigger a pro-inflammatory reaction in brain endothelial cells, potentially leading to alterations in BBB functionality [ 96 , 97 , 98 , 99 , 100 ].…”
Section: Challenges Of Delivering Prime Editors To the Brainmentioning
confidence: 99%